2021
DOI: 10.3389/fcvm.2021.701243
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Tricuspid Regurgitation: Pathophysiology, Incidence and Prognosis

Abstract: Tricuspid regurgitation (TR) can be divided into primary and secondary origins. Primary TR is mostly caused by infective endocarditis, leaflet perforation, entrapment after device placement and congenital abnormalities. The natural cause of secondary (functional) TR is not well-understood and underdiagnoses is likely. Because symptoms such as ascites, edema and hepatomegaly usually manifest at a late state, assessment of TR is challenging requiring a multiparametric approach. Secondary TR can be subdivided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Recently, echocardiographic studies have reported that different mechanisms of FTR would lead to different geometric changes in TA ( 17 ). Compared with ventricular FTR, atrial FTR is more dilated and has a more posteriorly displaced annulus ( 18 ), while pulmonary hypertension-related FTR correlates more significantly with leaflet tethering during RV elongation compared with atrial FTR ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, echocardiographic studies have reported that different mechanisms of FTR would lead to different geometric changes in TA ( 17 ). Compared with ventricular FTR, atrial FTR is more dilated and has a more posteriorly displaced annulus ( 18 ), while pulmonary hypertension-related FTR correlates more significantly with leaflet tethering during RV elongation compared with atrial FTR ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in three-dimensional (3D) echocardiography imaging, including machine learning algorithms, provide a more reliable and feasible examination of the right ventricle without geometrical assumptions [1,11]. Furthermore, the pathophysiology of RV function is often related to tricuspid regurgitation (TR) [12,13]. A mild degree of TR is highly prevalent and is usually considered a benign incidental finding on routine echocardiography [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, despite optimal medical management of primary cardiac pathology such as ischemic heart disease and/or cardiomyopathy, patients can still experience refractory congestive symptoms due to the progression of secondary valvular disease (tricuspid and/or mitral regurgitation). Tricuspid regurgitation (TR), especially secondary regurgitation, has been a trifled valvular pathology that has gained some attention in recent times as the milieu of chronic venous congestion and its detrimental effect on end-organ function is better understood ( 4 ). These patients are not usually favored for surgical valvotomy or valvular replacement due to perceived high surgical risk that is attributed to poor functional status, underlying disease process, recurrent exacerbations, and significant comorbidities.…”
Section: Introductionmentioning
confidence: 99%